2011
DOI: 10.1007/s10270-010-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Concern coverage in base station development: an empirical investigation

Abstract: Contemporary model driven development tools only partially support the abstractions occurring in complex embedded systems development. This article presents an interpretive case study in which architectural concerns important to seven engineers in a large product developing organization were compared to the views actually provided by the organization's models. The paper's main finding is an empirically grounded catalogue of architectural concerns for a large, complex embedded systems project, and an assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…They also report on the lack of organizational maturity in terms of which processes to use in combination with MDE, the difficulties in adapting existing skills to the new challenges of MDE and the unwillingness of the organization to change in order to make the most out of the transition into MDE. A previous study conducted at Radio can be found in [13]. Here the emphasis is on MDE in relation to architectural concerns (deployment, algorithms, performance etc.)…”
Section: Other Related Workmentioning
confidence: 99%
“…They also report on the lack of organizational maturity in terms of which processes to use in combination with MDE, the difficulties in adapting existing skills to the new challenges of MDE and the unwillingness of the organization to change in order to make the most out of the transition into MDE. A previous study conducted at Radio can be found in [13]. Here the emphasis is on MDE in relation to architectural concerns (deployment, algorithms, performance etc.)…”
Section: Other Related Workmentioning
confidence: 99%
“…Pareto et al [19] presents a catalogue of concerns related to embedded systems architecture that contains 114 variations of architecture. These variations were identified through an experimental study with seven systems engineers and the architecture variations were catalogued like models and/or text documents.…”
Section: Facet 3 -Semi-formal and Informal Modellingmentioning
confidence: 99%
“…Indeed, some practitioners did see productivity gains for product lines/families , where the generative tools and the bulk of the source models are reused across many applications . However, others have pointed out that the cost of modeling can outweight the benefits to be gained (eg, see the work of Pareto et al). The generated code tends to lack elegance and efficiency because it is not/cannot be “locally optimized.” In some cases, this had led practitioners to manually edit the generated code for performance‐criticial functions (see for example the works of Mohagheghi et al and Hutchinson et al).…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Indeed, some practitioners did see productivity gains for product lines/families, where the generative tools and the bulk of the source models are reused across many applications. [6][7][8] However, others have pointed out that the cost of modeling can outweight the benefits to be gained (eg, see the work of Pareto et al 23 ).…”
Section: Impact On Productivity and Skill Levelmentioning
confidence: 99%